2013
DOI: 10.1136/bmjqs-2013-001812
|View full text |Cite
|
Sign up to set email alerts
|

Human factors and ergonomics as a patient safety practice

Abstract: BackgroundHuman factors and ergonomics (HFE) approaches to patient safety have addressed five different domains: usability of technology; human error and its role in patient safety; the role of healthcare worker performance in patient safety; system resilience; and HFE systems approaches to patient safety.MethodsA review of various HFE approaches to patient safety and studies on HFE interventions was conducted.ResultsThis paper describes specific examples of HFE-based interventions for patient safety. Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
143
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(153 citation statements)
references
References 65 publications
0
143
0
10
Order By: Relevance
“…Studies indicated that using carpets, or other low-impact flooring solutions, did not show significant differences in reducing the risk of falls compared with a vinyl flooring (Hanger, 2017;Warren & Hanger, 2013); while Lachance et al's (2017) review concluded that compliant flooring was a promising strategy for preventing fall-related injuries. On the other hand, it is clear that ergonomic furniture, fixtures and equipment (FF&E), and anti-slip facilities are necessary to reduce falls, back pain and increase social interactions, and for safety reasons (Carayon, Xie, & Kianfar, 2014;Clarkson et al, 2004;Reiling et al, 2004).…”
Section: Final E-o-h Frameworkmentioning
confidence: 99%
“…Studies indicated that using carpets, or other low-impact flooring solutions, did not show significant differences in reducing the risk of falls compared with a vinyl flooring (Hanger, 2017;Warren & Hanger, 2013); while Lachance et al's (2017) review concluded that compliant flooring was a promising strategy for preventing fall-related injuries. On the other hand, it is clear that ergonomic furniture, fixtures and equipment (FF&E), and anti-slip facilities are necessary to reduce falls, back pain and increase social interactions, and for safety reasons (Carayon, Xie, & Kianfar, 2014;Clarkson et al, 2004;Reiling et al, 2004).…”
Section: Final E-o-h Frameworkmentioning
confidence: 99%
“…Work to apply human factors in healthcare to enhance systems and environments has shown the potential to enhance safety 15 .…”
Section: Introductionmentioning
confidence: 99%
“…135 Greater understanding of such human factors, specifically with regard to (i) human error, (ii) the role of health-care worker performance and (iii) the design of health-care technology, is increasingly recognised as core to patient safety. [136][137][138] But to be successful, this, too, necessitates careful consideration of the local context and the informal culture of clinical practice. 139 …”
Section: Team Workmentioning
confidence: 99%